Bell's Palsy Associated with SARS-CoV-2 Infection in a 2-Year-Old Child - Bsales, Serina; Olson, Birk; Gaur, Sunanda; Chefitz, Dalya; Carayannopoulos, Mary; Uprety, Priyanka; Esfahanizadeh, Abdolreza (Journal of Pediatric Neurology, 2021)
Bell's palsy (BP) is an acute, unilateral facial nerve palsy (FNP) that is a diagnosis of exclusion, sometimes associated with infectious causes. In this article, we described a previously healthy 2-year-old child patient who presented with left-sided facial droop, positive severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) real-time reverse transcription polymerase chain reaction (RT-PCR), positive SARS-CoV-2 immunoglobulin (Ig)-G antibody, and negative cerebrospinal fluid (CSF) SARS-CoV-2 (PCR and serology). This is the second reported pediatric case of BP in the setting of SARS-CoV-2, and the first in a child without comorbidities. Due to the positive antibody test, we presented the idea that SARS-CoV-2 could be a triggering factor of the FNP, possibly occurring in the later stages of disease.
Keywords: Bell's palsy; COVID-19; SARS-CoV-2; facial nerve palsy; facial asymmetry